Antiviral activity by lecithin-induced fengycin lipopeptides as a potent key substrate against Cucumber mosaic virus. (June 2021) - Kang, Beom Ryong; Park, Joon Seong; Jung, Woo-Jin
Abstract: In this study, the effect of different growth substrates on the production of biosurfactants in the PPL strain of Bacillus amyloliquefaciens— a biocontrol agent for diseases affecting pepper and tomato plants — and on the antiviral effect of the PPL strain on Cucumber mosaic virus (CMV)-infected pepper plants was investigated. The multifunctional PPL strain exhibited enhanced growth and increased production of biosurfactants upon lecithin supplementation and consequently exhibited potent anti-CMV activity. The enhanced anti-CMV activity of the lecithin-supplemented PPL culture could be attributed to the antiviral effect as well as to the upregulation of plant defense-related genes. Treatment with pure commercial fengycins elicited a defense response against CMV in pepper plants; this effect was similar to that observed upon treatment with the lecithin-supplemented PPL culture. To the best of our knowledge, this is the first study to report the antiviral activity of lecithin-induced fengycin lipopeptides. These results suggest that the growth substrate affects antimicrobial production by B. amyloliquefaciens PPL, and consequently its antiviral activity. Highlights: The culture medium upon lecithin supplementation improved the biomass and functions of Bacillus amyloliquefaciens PPL. The lecithin-induced fengycin lipopeptides suppressed the development of CMV in pepper plants. Bioactive peptides of fengycin contributed to the elicited defense response potential against CMV.